PEMANFAATAN “TALUY-JO” GUNA MENDUKUNG PENINGKATAN DAYA SAING USAHA EKONOMI PRODUKTIF DI KOTA KOTAMOBAGU - Olii Rahmat (COMVICE: Journal Of Community Service, 2024)
The government has made various efforts to improve the performance of Productive Economic Enterprises), including through the Ministry of Social Affairs of the Republic of Indonesia. It aims to increase family income and social welfare. This Community Service Activity aims to improve efficiency and market access for Productive Economic Enterprises using the Taluy-Jo e-commerce application in Kotamobagu City. The activity was carried out intensively, starting with a preliminary survey about the conditions of the fostered partners, a literature study, Focus Group Discussions with several stakeholders, and training on creating applications and using them by the fostered partners. This PKM activity is expected to provide an in-depth understanding of the impact of implementing e-commerce technology on UEP and provide strategic recommendations to increase their competitiveness. It can positively contribute to local economic development, UEP growth, and the development of e-commerce applications in the Kotamobagu City area.